A CONDIÇÃO NOS DIREITOS PORTUGUÊS E NORTE-AMERICANO. POSSIBILIDADE E IMPOSSIBILIDADE: Lurdes Vargas (De Legibus - Law Journal, 2021)
The present study develops a comparative analysis of the Portuguese and North American rights, seeking to determine whether it is admissible to introduce in a contract a clause that will condition all or part of the effects of that contract to the occurrence of a future and uncertain event. The conclusion being that both legal systems in this comparison offer such a solution, other questions are raised: If such a conditioning event is originally impossible or superveningly impossible, what happens to the clause and the contract? Is there a special regime that applies to these problems? What solutions does it offer? At the end of the study, it was it was found that the North American condition adapts to very different cases and so does its regime. Although imprecise in its limits, it has a regime of non-fulfillment and impossibility of the condition quite complete, offering very common-sense solutions. The Portuguese legal regime of the condition is more precise, apparently clearer, and the contours of the condition are also more precise. But the legal regime of impossibility of the condition is more rigid and when faced with concrete cases it does not always offer a clear and fair answer